Good Governance and Corruption in the View of Syafruddin Prawiranegara (1911-1989) - Mustapa, Hasan (International Journal of Psychosocial Rehabilitation, 2020)
The main problem of this research is that although the reform era has rolled since 1998, the issue of administrative malls in government has not been fully answered both at the conceptual and practical levels. This is due to factors causing irregularities in government administration and corruption that are so complex from the time of Soekarno’s Old Order (1959-1966), Suharto’s New Order (1966-1998) to the present. The purpose of this study was to find out how Syafruddin Prawiranegara (1911-1989) developed the concept of good governance and efforts to tackle corruption. This study uses text analysis related to Syafruddin Prawiranegara’s political thinking which is relevant to the issues of good governance and corruption. The researcher found that according to Syafruddin public trust could be achieved through the role of deliberative public administration, inclusive government and patterns of government collaboration and citizen interaction. The results of the study concluded that good governance in Syafruddin’s eyes needed transparency, accountability, intelligence and communication skills. Everything should be supported by consistency in handling corruption. The researcher recommends that the handling of corruption must start from fostering mental awareness of the bureaucracy through an ethical spiritual approach.